FALSAFAH ANGKOLA-MANDAILING “PODA NA LIMA” DITINJAU DARI PERSPEKTIF HADIS - Karnada Nasution (Amsal Al-Qur’an: Jurnal Al-Qur’an dan Hadis, 2024)
Poda nalima is a philosophy of life for the Mandailing people which tries to invite us to a clean life, both physically and spiritually clean. The contents of poda nalima are 1. Paias Rohamu (Clean Your Heart), 2. Paias Pamatangmu (Clean Your Body), 3. Paias Parabitonmu (Clean Your Clothes), 4. Paias Bagasmu (Clean Your House) and 5. Paias Pakaranganmu (Clean Prohibitions or your environment). Poda nalima is the idea of ​​the ancestors of the Mandailing tribe which still exists in today's life and is a guide or advice in living everyday life. This research uses qualitative methods and conducts field research (Field Research) sourced from the South Tapanuli community and supported by literature study (Library Research). With data collection tools in the form of interviews with traditional leaders, religious leaders, community leaders and one village official.